Metabolism via arginase or nitric oxide synthase: two competing arginine pathways in macrophages - Rath,M; Mueller,I; Kropf,P; Closs,EI; Munder,M (Frontiers in Immunology, 2014)
Macrophages play a major role in the immune system, both as antimicrobial effector cellsand as immunoregulatory cells, which induce, suppress or modulate adaptive immuneresponses. These key aspects of macrophage biology are fundamentally driven by thephenotype of macrophage arginine metabolism that is prevalent in an evolving or ongoingimmune response. M1 macrophages express the enzyme nitric oxide synthase, whichmetabolizes arginine to nitric oxide (NO) and citrulline. NO can be metabolized to furtherdownstream reactive nitrogen species, while citrulline might be reused for efficient NOsynthesis via the citrulline–NO cycle. M2 macrophages are characterized by expression ofthe enzyme arginase, which hydrolyzes arginine to ornithine and urea. The arginase pathwaylimits arginine availability for NO synthesis and ornithine itself can further feed into theimportant downstream pathways of polyamine and proline syntheses, which are importantfor cellular proliferation and tissue repair. M1 versus M2 polarization leads to opposing outcomesof inflammatory reactions, but depending on the context, M1 and M2 macrophagescan be both pro- and anti-inflammatory. Notably, M1/M2 macrophage polarization can bedriven by microbial infection or innate danger signals without any influence of adaptiveimmune cells, secondarily driving the T helper (Th)1/Th2 polarization of the evolving adaptiveimmune response. Since both arginine metabolic pathways cross-inhibit each other onthe level of the respective arginine break-down products andTh1 andTh2 lymphocytes candrive or amplify macrophage M1/M2 dichotomy via cytokine activation, this forms the basisof a self-sustaining M1/M2 polarization of the whole immune response. Understanding thearginine metabolism of M1/M2 macrophage phenotypes is therefore central to find newpossibilities to manipulate immune responses in infection, autoimmune diseases, chronicinflammatory conditions, and cancer.